Covered self‐expandable metal stent deployment promises safe neoadjuvant chemoradiation therapy in patients with borderline resectable pancreatic head cancer. Issue 1 (31st March 2013) - Kubota, Kensuke; Sato, Takamitsu; Watanabe, Seitaro; Hosono, Kunihiro; Kobayashi, Noritoshi; Mori, Ryutaro; Taniguchi, Koichi; Matsuyama, Ryusei; Endo, Itaru; Nakajima, Atsushi
<x xml:space="preserve">Abstract</x> Background Patients with borderline resectable pancreatic head cancer (BRPHC) have been treated with neoadjuvant chemoradiation therapy (NACRT) using metallic stents. The aim of the present study was to evaluate the efficacy and complications of covered self‐expanding metallic stents (CSEMS) during the NACRT and surgical period. Patients and Methods We reviewed the outcomes of patients with BRPHC, then divided them chronologically into three groups as follows. Group A: upfront surgery with plastic stent (PS) deployment; group B: PS deployment plus neoadjuvant chemotherapy (NAC) and/or NACRT; group C: CSEMS deployment plus NAC/NACRT. Patients were categorized as borderline resectable based on National Comprehensive Cancer Network Guidelines, 2010. Days to reintervention (DR), reintervention rate, and the rate of R0 and complications were studied. Safe margin‐negative resection (R0) surgery was defined as R0 surgery without reintervention during the NACRT period and no postoperative complications. Results DR were as follows. Groups A, B and C were 32, 55 and 97 days, respectively (P < 0.05). R0 surgery obtained in groups A, B and C was 53% (9/17), 100% (17/17) and 93% (14/15), respectively. CSEMS did not interfere with surgery. Safe R0 surgery obtained in groups B and C was 11% (2/19) and 67% (10/15), respectively (P < 0.05). Multivariate analysis showed that the odds ratio for safe R0 surgery was 16.210 (95% CI 2.457–106.962, P = 0.003) for CSEMS placement. Conclusion CSEMS should be considered to relieve symptomatic biliary obstruction in patients with BRPHC receiving NACRT in view of the high attainability rate of safe R0 surgery compared to that with PS deployment.